RESEARCH ON MECHANISM AND INFLUEBTIAL FACTORS OF TORSIONAL VIBRATION OF MAIN DRIVE ELECTROMECHANICAL COUPLED SYSTEM OF ROLLING MILL - GAO ChongYi; WEI YunPing; QIN HongXing; XIAO ChunYing; LI JianXiong (Jixie qiangdu)
The main drive system of rolling mill is a complicated electromechanical system,as the main device of transmitting motion and torque. The factor of electromechanical coupling is one of the important reasons for the abnormal variation of torsional vibration. The paper mainly researched that the dynamic analyses of the torsional vibration of main drive system of rolling mill. Comparative analysis the torsional vibration of main drive system is obtained between considering electromechanical coupling and not considering electromechanical coupling. Then,the mechanical and mathematical models of the main drive torsional vibration system are established. Based on Matlab/Simulink simulation,the unstable state of the main drive torsional vibration system is used to be studied,and then the influences of the uncertain parameters on the torsional vibration of main drive system are analyzed. The results could be revealed the oscillation law for the torsional vibration of main drive system of rolling mill and provided a theoretical foundation for the formulation of control strategy.